Cerebral Hemodynamic Failure Presenting as Limb-Shaking Transient Ischemic Attacks - Nedelmann, Max (S. Karger AG, 2011)
Limb-shaking transient ischemic attacks (TIA) may occur in patients with insufficient brain perfusion due to an underlying occlusive disease. We present the case of a 64-year-old patient who suffered from repetitive TIA presenting with shaking movements of the right-sided extremities and accompanying speech arrest. Symptoms are documented in the online supplementary video (www.karger.com/doi/10.1159/000327683). These episodes were frequently triggered in orthostatic situations. The diagnosis of limb-shaking TIA was established. The diagnostic workup revealed pseudo-occlusion of the left internal carotid artery, a poor intracranial collateral status and, as a consequence, an exhausted vasomotor reserve capacity. At ultrasound examination, symptoms were provoked by a change of the patient's position from supine to sitting. During evolvement of symptoms, a dramatic decrease of flow velocities in the left middle cerebral artery was observed. This case thus documents the magnitude and dynamics of perfusion failure in a rare manifestation of cerebral ischemic disease.